Epitheliotropic lymphoma-induced disseminated ulcerative dermatitis in a dog - Oakes, Vanessa J.; Carvallo, Francisco R. (Brazilian Journal of Veterinary Pathology, 2021)
A young adult, spayed female dog was presented for necropsy by animal control, with concerns for abuse in the form of chemical burns.